Turbulent pipe flow of a drag reducing, rigid “rod-like” polymer solution - Japper-Jaafar, Azuraien (2009)
Fully-developed turbulent pipe flow of an aqueous solution of a rigid “rod-like” polymer, scleroglucan, at concentrations of 0.005% w/w and 0.01% w/w has been investigated experimentally. Fanning friction factors were determined from pressure-drop measurements for the Newtonian solvent (water) and the polymer solutions and so levels of drag-reduction for the latter. Mean axial velocity u and complete Reynolds normal-stress data, i.e. u', v' and w', were measured by means of a laser Doppler anemometer at three different Reynolds numbers for each fluid. The measurements indicate that the effectiveness of scleroglucan as a drag-reducing agent is only mildly dependent on Reynolds number. The turbulence structure essentially resembles that of flexible polymer solutions which also lead to low levels of drag reduction.